Protein receptor-independent plasma membrane remodeling by HAMLET: a tumoricidal protein-lipid complex - Nadeem, Aftab (2015)
A central tenet of signal transduction in eukaryotic cells is that extra-cellular ligands activate specific cell surface receptors, which orchestrate downstream responses. This ‘’protein-centric” view is increasingly challenged by evidence for the involvement of specialized membrane domains in signal transduction. Here, we propose that membrane perturbation may serve as an alternative mechanism to activate a conserved cell-death program in cancer cells. This view emerges from the extraordinary manner in which HAMLET (Human Alpha-lactalbumin Made LEthal to Tumor cells) kills a wide range of tumor cells in vitro and demonstrates therapeutic efficacy and selectivity in cancer models and clinical studies. We identify a ‘’receptor independent” transformation of vesicular motifs in model membranes, which is paralleled by gross remodeling of tumor cell membranes. Furthermore, we find that HAMLET accumulates within these de novo membrane conformations and define membrane blebs as cellular compartments for direct interactions of HAMLET with essential target proteins such as the Ras family of GTPases. Finally, we demonstrate lower sensitivity of healthy cell membranes to HAMLET challenge. These features suggest that HAMLET-induced curvature-dependent membrane conformations serve as surrogate receptors for initiating signal transduction cascades, ultimately leading to cell death.